Risk factors for first-trimester spontaneous abortion and the role of preconception care - Podilyakina, Yuliya; Stabayeva, Leila; Kulov, Dusentay; Kamyshanskiy, Yevgeniy; Amirbekova, Zhanna; Stundžienė, Rasa; Zhamantayev, Olzhas (Frontiers in Global Women's Health, 2025)
BackgroundSpontaneous abortion in the first trimester is a common adverse pregnancy outcome with significant implications for maternal health and public health practice. The description of associations with modifiable factors, including preconception care, can aid in planning strategies to improve pregnancy outcomes.MethodsA retrospective analysis was conducted using data from 1,526 women, divided into two groups based on pregnancy outcomes: spontaneous abortion in the first trimester and live births. Binary and multivariate logistic regression analyses were performed to identify associations between factors (including preconception care) and the risk of spontaneous abortion in the first trimester.ResultsAge >35 years [[OR] = 2.02, 95% [CI] = 1.49–2.75], obesity [[OR] = 1.81, 95% [CI] = 1.12–2.91], and a history of spontaneous abortion [[OR] = 1.57, 95% [CI] = 1.01–2.43] were associated with higher odds of spontaneous abortion in the first trimester, whereas preconception care was associated with lower odds of spontaneous abortion in the first trimester [[OR] = 0.58, 95% [CI] = 0.45–0.75].ConclusionThe findings may help clinicians stratify pregnant women who require additional monitoring and pre-pregnancy interventions. From a public health perspective, integrating preconception care into routine health services can enhance maternal and neonatal outcomes, reduce healthcare costs, and improve health equity by targeting vulnerable populations. However, the results should be interpreted as associations, and prospective studies are needed to assess the potential effects of preconception care on spontaneous abortion in the first trimester.